2016
DOI: 10.1080/1369118x.2016.1153126
|View full text |Cite
|
Sign up to set email alerts
|

The work that visualisation conventions do

Abstract: This paper argues that visualisation conventions work to make the data represented within visualisations seem objective, that is, transparent and factual. Interrogating the work that visualisation conventions do helps us to make sense of the apparent contradiction between criticisms of visualisations as doing persuasive work and visualisation designers' belief that through visualisation, it is possible to 'do good with data' (Periscopic, 2014). We focus on four conventions which imbue visualisations with a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(138 citation statements)
references
References 32 publications
1
125
0
7
Order By: Relevance
“…This entanglement is productive for thinking about how data are experienced. As we have noted elsewhere with others (Kennedy et al, 2016), unlike other visual imagery like photography, the raw material of visualisations does not exist in a perceptually available form outside of their design. Data come into being through visual design; that is, through the visual elements chosen to present them.…”
Section: )mentioning
confidence: 99%
“…This entanglement is productive for thinking about how data are experienced. As we have noted elsewhere with others (Kennedy et al, 2016), unlike other visual imagery like photography, the raw material of visualisations does not exist in a perceptually available form outside of their design. Data come into being through visual design; that is, through the visual elements chosen to present them.…”
Section: )mentioning
confidence: 99%
“…A diferencia de las figuras de experticia que utiliza regularmente la cobertura periodística en otros medios, como la televisión o la prensa, en la visualización de datos se hacen presentes expertos provenientes de afuera del campo deportivo que, desde el manejo exclusivo de su conocimiento especializado, brindan una mirada profunda del evento deportivo. En el reforzamiento de esta mirada ayudan los componentes de la síntesis informativa y visual que muestran Kennedy et al (2016).…”
Section: Conclusionesunclassified
“…As such, diagrams as graphical, multimodal devices of future-oriented knowledge work implicate assumptions about the knowledgeability, numeracy, and responsiveness of publics. As Kennedy et al (2016) have shown, the underlying optimistic yet flawed belief that visualizations foster data transparency and awareness is shared among data practitioners. Thus, although many visualization designers acknowledge that design conventions involve a number of critical restrictions, they nevertheless hold on to the idea that they can achieve some kind of accuracy in the representation of data and data-driven insights.…”
Section: Diagrammatic Displays In Predictive Data Journalismmentioning
confidence: 99%